The Compositionally Distinct Cyanobacterial Biocrusts From Brazilian Savanna and Their Environmental Drivers of Community Diversity - Machado-de-Lima, Náthali Maria [UNESP]; Fernandes, Vanessa Moreira Câmara; Roush, Daniel; Velasco Ayuso, Sergio; Rigonato, Janaina; Garcia-Pichel, Ferran; Branco, Luis Henrique Zanini [UNESP] (Frontiers, 2019)
The last decade was marked by efforts to define and identify the main cyanobacterial players in biological crusts around the world. However, not much is known about biocrusts in Brazil’s tropical savanna (cerrado), despite the existence of environments favorable to their development and ecological relevance. We examined the community composition of cyanobacteria in biocrusts from six sites distributed in the Southeast of the country using high throughput sequencing of 16S rRNA and phylogenetic placement in the wider context of biocrusts from deserts. Sequences ascribable to 22 genera of cyanobacteria were identified. Although a significant proportion of sequences did not match those of known cyanobacteria, several clades of Leptolyngbya and Porphyrosiphon were found to be the most abundant. We identified significant differences in dominance and overall composition among the cerrado sites, much larger than within-site variability. The composition of cerrado cyanobacterial communities was distinct from those known in biocrusts from North American deserts. Among several environmental drivers considered, the opposing trend of annual precipitation and mean annual temperature best explained the variability in community composition within Brazilian biocrusts. Their compositional uniqueness speaks of the need for dedicated efforts to study the ecophysiology of tropical savanna biocrust and their roles in ecosystem function for management and preservation.
Keywords: aridity; biocrust; cerrado savanna; cyanobacteria; Leptolyngbya; Porphyrosiphon